Study of the effect of changes in cell output temperature on the net efficiency of solid oxide fuel cell power generation - Handrea Bernando Tambunan; Ignatius Riyadi Mardiyanto; Lina Troskialina; Sri Paryanto Mursid; Lidya Elizabeth; Dhyna Analyes Trirahayu; Retno Dwijayanti (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
Solid oxide fuel cell (SOFC) power plants offer a promising pathway toward highly efficient energy conversion compared to conventional systems. This study explores the impact of output temperature variations on system performance through simulation analysis. The results demonstrate that increasing the temperature difference between the fixed input (700 °C) and the cell output significantly enhances net efficiency, while gross efficiency remains relatively stable. At an output temperature of 875 °C, the system achieves a net efficiency approaching 50% and a gross efficiency of approximately 61%. These findings emphasize the critical role of output temperature in determining overall system efficiency and highlight the importance of thermal management in SOFC operation.